2020
DOI: 10.1007/s00170-019-04832-6
|View full text |Cite
|
Sign up to set email alerts
|

Effective FE models for simulating the elasto-mechanical characteristics of forming machines

Abstract: The elasto-mechanical characteristic of forming machines is crucial for a variety of forming processes. Numerical simulations are to be performed to understand the complex interaction between process, forming tool, and machine. The machine's elastic fingerprint depends on its design, accuracy of the components, and mounting conditions. Models only based on data of the machine design are limited. Therefore, effective FE models are to be developed to transfer the physical structure into a digital representation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Full representations of presses will result in very large FE models. Presses can however be represented by various measuring and modeling techniques [6,8,[17][18][19][20][21]. Measuring and characterizing a press cushion is more challenging.…”
Section: Methods For Smf Simulations With Elastic Diesmentioning
confidence: 99%
See 1 more Smart Citation
“…Full representations of presses will result in very large FE models. Presses can however be represented by various measuring and modeling techniques [6,8,[17][18][19][20][21]. Measuring and characterizing a press cushion is more challenging.…”
Section: Methods For Smf Simulations With Elastic Diesmentioning
confidence: 99%
“…Another reason is the lack of die CAD models before the later stages of stamping projects. Previous research during the last couple of decades indicated large benefits if elastic dies and presses are included in SMF simulations [1][2][3][4][5][6][7][8]. The benefits of simulations with elastic tools are also seen in related manufacturing techniques using dies and presses.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research and experience points to many advantages if sheet metal forming is simulated with elastic dies [1][2][3][4][5][6][7][8]. Some areas that are enabled by simulations with elastic dies are virtual spotting, improved digital twins, and improved production support.…”
Section: Introductionmentioning
confidence: 99%
“…The different simulation methods have in common that they, apart from blank and elastic die, need to include numerical representations of the elastic stamping press structure, e.g. [5][6]. The disadvantage is that they can be very computationally expensive when large sections of the stamping press are modeled.…”
Section: Introductionmentioning
confidence: 99%